International Postdocs: Educational Migration and Academic Production in a Global Market - Cantwell, Brendan (The University of Arizona., 2009)
This dissertation is a qualitative investigation into international postdoctoral employment in life science and engineering fields at universities in the United States and United Kingdom. Data were gathered through 49 in-depth, semi-structured interviews with international postdocs, faculty members who have supervised international postdocs from abroad at two universities in the US and two universities in the UK. The number of postdoctoral appointments has increased dramatically over the past decade, as has the share of these appointees who come from aboard. Yet few studies have investigated what is underlying this growing trend. By examining interactions between structure and agency at local, global and national levels, this study explored the roles that international postdocs play in academic production and the process by which they become mobile. Theory on globalization, higher education policy and models of academic production guide this study. Findings show that international postdocs are becoming scientific employees, rather than trainees, who are incorporated into capitalist modes of academic production as low-cost, high-yield scientific workers. Universities and individual faculty members seek international postdocs because of their contributions to research production; however, few postdocs have the opportunity to move into tenure-tracked faculty jobs. For international postdocs, becoming mobile is an individual process that is often constructed by individuals who negotiate home country academic policies in a global academic market. Mobility is a multi-stage process that begins with the potential to become mobile and is realized by actual mobility, which occurs through a transnational space produced by international journals that define global science.